Bioactive and Functional properties of gelatin peptide fractions obtained from sea bass (Dicentrarchus labrax) skin - Tekle, Sefik; Bozkurt, Fatih; Akman, Perihan Kubra; Sagdic, Osman (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
Fish skin is one of the most common resources of gelatin, which can be hydrolyzed bioactive peptides. In this study, gelatin from sea bass skin (SBS) was hydrolyzed with flavourzyme (R) to obtain peptide fractions with different molecular weights and determined their bioactive and functional properties. All peptide fractions obtained showed antioxidant activity (DPPH and FRAP). The bass gelatin peptide fraction 1 (BPI) ( = 10 kDa) peptide fraction showed an excellent fat binding capacity (9.39 mL/g). Enzymatic hydrolysis decreased emulsifying and foaming capacity of gelatin while increasing its fat binding capacity. In particular, antioxidant and anticancer activities of peptide fractions with low molecular weight were found to be high. The results demonstrated that gelatin and hydrolysates from the SBS offer an important alternative as a functional food ingredient for food technology.
Keywords: sea bass skin; gelatin peptide fractions; bioactive peptides; in-vitro cytotoxic activity; functional properties; FISH-PROTEIN; BY-PRODUCTS; ANTIOXIDANT; HYDROLYSIS; BOVINE; OPTIMIZATION; PURIFICATION; EXTRACTION; MUSCLE; Food Science & Technology